2017
DOI: 10.1111/lam.12739
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of iturin A production inBacillus subtilisZK0 by overexpression of thecomAandsigAgenes

Abstract: This study provides new perspectives on improving iturin A production by Bacillus subtilis. Our newly engineered strains could be applied to commercial fermentation by enhancing yields of iturin A and reducing the rate of 'stuck fermentation'. Increased production would facilitate more widespread application of this powerful antibiotic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…ComA and DegU, as signal regulators in the two-component system, control many processes of cells, including biofilm and competence formation, bacterial motility and antibacterial substances synthesis (Hamoen et al 2003;Harshey 2003;Kobayashi 2007;Koumoutsi et al 2007;Verhamme et al 2007;Mariappan et al 2012;Wang et al 2015;Zhang et al 2017). As an important protein controlling spore formation, Spo0A played a key regulation role in the synthesis of iturin A and bacilysin (Yazgan Karatas ß et al 2003; Rahman et al 2006;Boguslawski et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ComA and DegU, as signal regulators in the two-component system, control many processes of cells, including biofilm and competence formation, bacterial motility and antibacterial substances synthesis (Hamoen et al 2003;Harshey 2003;Kobayashi 2007;Koumoutsi et al 2007;Verhamme et al 2007;Mariappan et al 2012;Wang et al 2015;Zhang et al 2017). As an important protein controlling spore formation, Spo0A played a key regulation role in the synthesis of iturin A and bacilysin (Yazgan Karatas ß et al 2003; Rahman et al 2006;Boguslawski et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The construction of expression vectors was based on pHT43 (Zhang et al 2017). The primers used for construction of expression vectors are presented in Table S2.…”
Section: Construction Of Strainsmentioning
confidence: 99%
“…Second, positive or negative regulators of cyclic lipopeptides, such as the ComP/ComA two-component system, DegU, Sfp or YczE, PerR, and Rap proteins and Phr peptides, might be involved in a mechanism that increases iturin production in the surfactin-less mutant strain. ComP/ComA, Sfp, PerR, and Phr are positive regulators of srfA transcription [ 11 , 45 48 ], and overexpression of the comA and sigA genes was shown to improve iturin production [ 49 ]. In addition, DegU and YczE positively regulate the synthesis of bacillomycin D in Bacillus amyloliquefaciens strain [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an attempt was made to delete the regulator gene abrB to enhance the expression of iturin A synthetase by relieving the repression caused by AbrB on PbacA. As per previous studies, iturin A production from B. subtilis ZK0 and wild-type B. subtilis ZEB01 was found to be 0.005 g/L, which increased to 0.215 g/L by the simultaneous overexpression of the comA and sigA regulatory genes in B. subtilis ZK0 [ 27 ]. Dang et al (2019) [ 28 ] reported 0.037 g/L of iturin A when a strong promoter was inserted into the upstream of itu operon for the transcription enhancement of iturin A genes.…”
Section: Resultsmentioning
confidence: 83%